Uso de fitorreguladores para controle do desenvolvimento vegetativo e aumento da frutificação em macieira e pereira. - Hawerroth, Fernando José (2010)
The proper balance between vegetative growth and frutification in pome fruit species such as apple and pear, it is essential to increase production efficiency and improving fruit quality. In this sense, control of vegetative growth and frutification increase are needed in the management of these species, which may be obtained by use of growth regulators. The objective of this study was to evaluate the control of vegetative growth and frutification increase of apple and pear orchards in the Southern Brazil climatic conditions in response to the use of growth regulators. For this, three experiments were carried out in this research. In the first experiment, different concentrations of prohexadione calcium were evaluated in 'Imperial Gala' and 'Fuji Suprema' apple trees, grafted on Marubakaido rootstock with M9 interstock, in an orchard located in Fraiburgo/SC. The treatments (0, 165, 330, 495, 660, and 990 g ha-1 prohexadione calcium) were applied during the vegetative growth in 2008/2009 and 2009/2010 growing seasons. The concentrations corresponding to each treatment were applied split into three parts. The first application was done when the shoots of the control treatment showed growth of 10 cm. The second and third applications were made at 30 and 60 days after the first application, respectively. The prohexadione calcium was effective in controlling vegetative growth of apple trees 'Imperial Gala' and 'Fuji Suprema', reducing the total weight and average weight of pruned shoots, as well as the average shoot length, in the Southern Brazil climatic conditions. The use of prohexadione calcium at concentrations ranging from 165 to 330 g ha-1 increased the fruit production of 'Imperial Gala' apples, but high concentrations of this growth regulator tends to reduce the fruit production, especially in 'Fuji Suprema' apples. The reduction of vegetative growth by the use of prohexadione calcium contributed to increase calcium content in fruits of 'Fuji Suprema'. The second experiment was carried out in Pelotas/RS, using 'Hosui' pears grafted on Pyrus calleryana rootstock. Different 8 concentrations of prohexadione calcium were evaluated (0, 275, 550, and 825 g ha- 1), being half the concentration corresponding to each treatment applied when the shoots had between 5 to 10 cm in length, and the remainder applied 30 days after the first application. The use of prohexadione calcium was effective in controlling the vegetative growth of 'Hosui' pears, decreasing the need for winter pruning by reducing the total weight and the number of shoots pruned. The control of vegetative growth by use of prohexadione calcium determined increase the productive capacity of 'Hosui pears, especially at concentrations ranging from 450 to 750 g ha-1. The aim of the third experiment was to evaluate the effectiveness of thidiazuron, gibberellic acid, prohexadione calcium and combination of these substances on frutification increase of 'Shinseiki' asian pears. The following treatments were applied at full bloom: 1. control (no application); 2. thidiazuron (TDZ) 20 mg L-1; 3. gibberellic acid (GA) 20 mg L-1; 4. prohexadione calcium (PCa) 600 mg L-1; 5. PCa 600 mg L-1 + TDZ 20 mg L-1; 6. PCa 600 mg L-1 + AG 20 mg L-1; e 7. AG 20 mg L-1 + TDZ 20 mg L-1. The application thidiazuron at 20 mg L-1, gibberellic acid at 20 mg L-1 and the combination of these substances during the full bloom increased significantly the frutification and the fruit production of 'Shinseiki' pears. The prohexadione calcium, when sprayed at flowering alone or in combination to thidiazuron and gibberellic acid, was not effective to increase the fruit set and fruit production. The use of growth regulators on flowering decreased the number of seeds per fruit.